2013
DOI: 10.5171/2013.264063
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after a First- ever Ischemic Stroke Development of a Clinical Prediction Rule

Abstract: Background: Cumulative risk of stroke recurrence is about 26% at five years, with overall mortality rate of 38%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…In the 16 studies identified the cumulative risk of stroke recurrence in 9115 patient survivors are as follows: 3.1% at 30 days, 11.1% at 1 year, 26.4% at 5 years and 39.2% at 10 years. Our results are consistent with the previous finding that the risk of stroke recurrence is highest in the first year following a first ever-ischemic stroke [4][5][6]. In this study, the odds of a stroke recurrence in the first year after the index stroke is 2.4 times higher than in subsequent years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the 16 studies identified the cumulative risk of stroke recurrence in 9115 patient survivors are as follows: 3.1% at 30 days, 11.1% at 1 year, 26.4% at 5 years and 39.2% at 10 years. Our results are consistent with the previous finding that the risk of stroke recurrence is highest in the first year following a first ever-ischemic stroke [4][5][6]. In this study, the odds of a stroke recurrence in the first year after the index stroke is 2.4 times higher than in subsequent years.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported in hospital-based data that the over-all risk of stroke recurrence within five years after a first episode is approximately between 15-40% [3,4]. Within the first year after the initial stroke, the risk of stroke recurrence is higher (between 6-14%) as opposed to risk in subsequent years (4% annually) [4][5][6]. The maximum incidence of recurrent stroke is in the first 30 days after initial stroke [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes are two to three times more likely to have ischemic stroke when compared with nondiabetic individuals [28] . Diabetes mellitus was associated with 26.25% of ischemic stroke [29] .…”
Section: Alemayehu and Birhanesilasiementioning
confidence: 99%
“…Twelve of our patients had ischemic heart disease with eight patients having atrial fibrillation. Atrial fibrillation is arguably the most important cardiac risk factor for stroke [29] .…”
Section: Alemayehu and Birhanesilasiementioning
confidence: 99%
“…Patients with a recent ischemic stroke are at risk for a second ischemic stroke with reported 1-year-incidence rates ranging from 8% to 14% [1][2][3]. In contrast to patients with transient ischemic attack (TIA), predictors of recurrent ischemic stroke in patients with a recent ischemic stroke are less well known.…”
Section: Introductionmentioning
confidence: 99%